1994
DOI: 10.1093/infdis/169.5.1108
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Human Papillomavirus DNA Detection in Human Immunodeficiency Virus Type 1-Seropositive and -Seronegative Women

Abstract: Cericovaginal lavage samples from 124 human immunodeficiency virus type 1 (HIV-1)-seropositive and 126 HIV-1-seronegative women were collected monthly for 8 months and tested for human papillomavirus (HPV) DNA. The estimated prevalence of HPV was 42.8% in HIV-1-seropositive and 13.4% in -seronegative women (P < .001). There was no significant difference in HPV DNA detection in HIV-1-seropositive women with CD4 cell counts of < 300/mm3 (50% HPV-positive), 300-499/mm3 (36.4% HPV-positive), or > or = to 500/mm3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
26
0
5

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(35 citation statements)
references
References 0 publications
4
26
0
5
Order By: Relevance
“…(26,32,33) and to augment the relative risk of cervical and anal carcinoma (11,12). However, we and others have pointed out that relatively few squamous invasive cancers develop in tritherapy untreated HIVinfected population despite the high incidence of high-grade CIN (22).…”
Section: Apoptosis and Viruses In Intraepithelial Cervical Lesionsmentioning
confidence: 99%
“…(26,32,33) and to augment the relative risk of cervical and anal carcinoma (11,12). However, we and others have pointed out that relatively few squamous invasive cancers develop in tritherapy untreated HIVinfected population despite the high incidence of high-grade CIN (22).…”
Section: Apoptosis and Viruses In Intraepithelial Cervical Lesionsmentioning
confidence: 99%
“…Furthermore, patients infected with human immunodeficiency virus (HIV) have a higher prevalence of HPV infection and malignant anogenital lesions. In HIV-1-positive women, Vernon et al (56) showed that the more immunocompromised is the patient, the more likely she is to carry persistent HPV infections.…”
Section: Immunological Response Against Hpvmentioning
confidence: 99%
“…HIV-seropositive women who were colposcopically normal had a sevenfold-greater amount of HPV DNA than HIV-seronegative women (18). This conclusion was confirmed by a third group measuring HPV DNA in selfobtained vaginal swabs (11) but was not reached by a fourth group (16). HPV viral load also varied with age (11).…”
mentioning
confidence: 91%
“…The assay we used was demonstrated to be specific for HPV-16 and does not cross-react with other HPV types (6,7,14). Several studies reported a higher quantity of HPV DNA in HIVseropositive than HIV-seronegative women but did not evaluate the impact of HIV-induced immunosuppression on HPV viral load (5,11,12,16,18). One of these studies demonstrated that the amount of HPV DNA increased in HIV-negative and HIV-seropositive women with the presence and grade of cervical lesions (18).…”
mentioning
confidence: 99%